ANALYSIS OF THE INFLUENCE OF LEADERSHIP, COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE EFFECTIVENESS AT THE DEPARTMENT OF CULTURE AND TOURISM TAPIN DISTRICT - Rahmiati, Rahmiati; Muhamamad Ramadhan; I Gede Putu Suardana (Jurnal Ekonomi, 2020)
Human resources are a central figure in the organization. The central figure is a leader and employee. Organizations must have employees who are knowledgeable and skilled as well as efforts to manage the agency as optimally as possible so that the effectiveness of employee performance increases so that management activities run well. This study aims to determine the effect of leadership on performance effectiveness, the effect of competence on performance effectiveness, the effect of work discipline on performance effectiveness and to find out which variables are more dominant in influencing performance effectiveness. This research method is a descriptive analysis method with a quantitative approach using a Google Form-based questionnaire distribution technique with a total of 40 respondents. The data analysis method used is Multiple Linear Regression Analysis. The results showed that the Leadership Variables (X1), Competence (X2), and Work Discipline (X3) had a significant simultaneous effect on the Employee Performance Effectiveness variable (Y) at the Department of Culture and Tourism of Tapin Regency. Furthermore, the Leadership Variable (X1), and Competence (X2) have no partially significant effect, but the Work Discipline variable (X3) has a partially significant effect on The Effectiveness Of The Performance of the Tapin Regency Culture and Tourism Office. Meanwhile, the Competency Variable (X2) does not have a dominant significant effect on The Effectiveness Of The Performance of the Department of Culture and Tourism of Tapin Regency.